ANALISIS CITRA ALOS AVNIR-2 DAN SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK PENGEMBANGAN RUANG TERBUKA HIJAU (Kasus Studi : Kota Surakarta dan Sekitarnya) - , OHIRA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Advanced Land Observing Satellite (ALOS) Advanced Visible and Near Infrared Radiometer type 2 (AVNIR-2) sensor with a spatial resolution of 10 meters is one sources of remote sensing data are used in various purposes, especially spatial analyzes of land cover monitoring activities. ALOS AVNIR-2 image has become the main source of data in the study. aims of this research are: 1)to analyze ALOS AVNIR-2 image to obtain the parameters of green open space development planning in Surakarta area: 2) to analyze the balance of green open space in Surakarta area, and 3) to analyze The the requirement and the direction of green open space development in Surakarta area. Analysis of land use of ALOS AVNIR-2 image using maximum likehood method to obtain green open space in the study area, while the availability of oxygen produced by green open space using Gerrarkisâ method approach. Oxygen demand is obtained by using the Wisesaâs method (1988). Green open space requirement is calculated by using Gerrarkisâ method approach based on the analysis of oxygen demand. The direction of green open space development based on the spatial analysis using overlay method with hierarchical weighted quantitative approach in a Geographic Information Systems (GIS). The analysis result of the land use showed green open space in the study area in 2009 amounted to 969 acres, to obtain oxygen availability of 500,682.77 kg/hr. The calculation of the oxygen demand based on population, vehicles and industries showed that the amount of fresh oxygen that should be produced in the year 2009 amounted to 936,364.60 kg/hr. Based on the analysis of oxygen demand, the green open space in the study area in 2009 amounted to 1,849.61 hectares. The analysis result of the direction of green open space development indicates the space area that should become a âpriorityâ for the supply of green open space, especially in the administrative region of Surakarta is Pajang Village, Sondakan, Laweyan, Penumping, Baluwarti, Joyosuran, Joyotakan, Kemlayan, Keprabon, Pasar Kliwon, Kepatuhan Wetan, Ketelan, Sudiroprajan, Penularan, parts of Karangasem, Jajar parts, parts Kerten Beyond the administrative area of Surakarta Urban Sranggahan, Makamhaji, most of Banaran and Madugondo, as well as a small area of green space Ngringo through the election of green open space varieties which is possible to be provided.